Violations of civil use of drones in the Gulf Cooperation Council countries and their penalties - Alkahf, Marwan Sharif (Journal of Economic, Administrative and Legal Sciences, 2022)
A drone is a small flying machine that it could fly in the air at law altitude with small engines and remotely could be piloted. It doesn’t need to inform the control towers or a helipads. Actually It began with military experiments and later on has been used by civilians, recreational and commercial means, and even a criminal tool.Laws has been set out to prevent it, and then gradually regulated its various uses for it.Its use has spread throughout the Gulf Cooperation Council countries, and that made an urgent need to study the old aviation laws and regulations that did not mention the drone. The modern Gulf laws and regulations stipulated the criminalization of drone uses, and punishments for violators has been set.. The policy of these countries in criminalization and punishment has been varied Penalties (, financial fines and some administrative penalties) were imposed on them.The research methods: We followed the comparative analytical descriptive method aiming to identify the violations and the penalties of procession and use of the drone in civilian areas.
Keywords: drone; criminal legislation; right to privacy; penalty for violation; Civil Aviation Authority; airspace